Disharmoni Hukum Waris Tanah di Nusa Tenggara Timur: Analisis Yuridis Putusan Pengadilan Negeri Kupang jo. Mahkamah Agung Nomor 1505 K/Pdt/2020 dalam Sengketa Ahli Waris Konay - Rayi Kharisma Rajib; Nazwa Ramadhani Mohamad; Istidiani Rizka Putri Widi (JURNAL ILMIAH NUSANTARA, 2026)
The customary land inheritance dispute of the Konay family in Kupang City, East Nusa Tenggara, culminating in Supreme Court Decision Number 1505 K/Pdt/2020, represents a structural tension between state law and customary law as living law within Indonesia’s legal system. Employing a normative legal method through case and conceptual approaches, this study analyzes the construction of the judges’ ratio decidendi and examines the extent to which the decision accommodates the existence of customary law in determining inheritance subjects. The analysis reveals that the ratio decidendi was constructed upon three hierarchical pillars: proof of genealogical relations, validation of prior judgments dating to 1951, and affirmation that the plaintiff lacked a valid legal basis. This construction reflects the dominance of legal positivism, reducing customary law’s complexity to formal evidentiary standards, thereby producing a phenomenon of forced formalization of adat. The decision recognizes the land’s status as ancestral clan land only rhetorically, without transforming it into a substantive foundation of legal reasoning. The disharmony is structural in nature, reflecting the persistent gap between the normative recognition of customary law and its judicial implementation in Indonesian court practice.